Implementation and Guarantee of Human Right to Rest in the System of Modern International Relations - Dordyak, Oksana (European Scientific Journal, ESJ, 2017)
This article analyzes the main challenges faced by tourists during the implementation of their right to rest. Various measures taken by states for strengthening national security are arising out of numerous terrorist threats and increasing illegal migration. All these measures are an obstacle to the effective development of tourism. Consumers and producers of travel services are forced to exercise their activity by taking into account many barriers standing in their way. Everyone's right to rest includes the right of freedom of movement, the right to liberty and personal inviolability, the right to a standard of living necessary for the maintenance of health and welfare etc. All these rights are guaranteed by major international legal instruments. Along with these rights, they contain provisions that restrict them. The article examines the main limitation of the above rights and their causes. The author explores scientific review of restrictions on the rights of freedom of movement and migration law of modern states. Violations of Human Rights are analyzed based on the example of cases reviewed by the European Court of Human Rights and the Court of Justice of the European Union. Security and human rights are two key issues that the international community is now trying to combine in regulation without any harm to anyone. The selectivity of modern visa policies provides the basis for the appearance of discrimination. This, however, is not recognized and condemned by international law. Creation of the unified international legal rules based on respect of human rights and security guarantees will facilitate the development of tourism and economy growth of developed and developing countries.